NATIONAL MODEL OF EDUCATION IN THE REPUBLIC OF KAZAKHSTAN AS THE KEY TO REALIZE THE NATIONAL IDENTITY - Malgazhdarova, T.G. (Scientific Journal of Pedagogy and Economics, 2020)
This article presents new education system in modern Kazakhstan, which is being formed, focused on the world educational space in the conditions of globalization. This process is accompanied by significant changes in pedagogical theory and practice. The transformation in the education system of Kazakhstan, as reflected in the Law of the Republic of Kazakhstan “On education”, “State Program of Education Development of the Republic of Kazakhstan for 2016-2019 years”, responsible include the entire teaching community in the process of creating of new model of education in Kazakhstan. Analyzing the practice of education reform in the different countries of the world, we can identify several key points that will contribute to changes in the education system of the XXI century: paying special attention to the higher education; development of each student, in accordance with their attitudes and abilities, individualization and differentiation of learning, development of critical thinking, the ability to reflexive assessment of their own achievements; training in conditions of inequality of starting positions of students (social, language, religious); development of students’ self-realization skills, self-study, study of motivation issues; changes in the approach to evaluating educational achievements, wider use of criteria-based assessment, changes in the content approach to summative assessment and its goals; using new approaches in teaching and learning; changing the vision of the professional development of leading teachers. All these key directions are reflected in the content of the republic’s education renewal. There is the change in the educational paradigm, offers the variety of the educational content and pedagogical technologies, new modern pedagogical concepts and ideas.